Defence industrial cooperation in the European Union the state, the firm and Europe - Fiott, Daniel 1982- (Routledge, 2019)
"This book provides an empirical understanding of how EU-level defence industrial cooperation functions in practice. Using the Liberal Intergovernmental theoretical model, the book argues that while national economic preferences are an essential factor of government interests they only explain part of the dynamic that leads to the development of defence industrial policy at EU level. Moving beyond a simple adumbration of economic preferences, it shows how the EU's institutional framework and corpus of law are used by governments to re-affirm their position as the ultimate arbiter and promoter of national economic preferences in the defence industrial sector. To this end, the work asks why and how EU member state governments, European defence firms, and EU institutions developed EU-level defence industrial policy between 2003 and 2009. The book also analyses significant policy developments, including the establishment of a European defence agency and two EU directives on equipment transfers and defence procurement. This book will be of much interest to students of EU policy, defence studies, security studies and international relations in general"--
Keywords: Defense industries / Government policy / European Union countries; European cooperation